LINGUOCULTURAL ASPECT OF IDIOMATIC COMPOUND WORDS - Azimova , Nigora Ilxomovna (Educational Research in Universal Sciences, 2023)
The present article is devoted to investigation of English and Uzbek idiomatic expressions or phraseological units which contain culture- related information. They were divided into main groups: idiomatic expressions with the structure of knowledge related to religion, myths and legends, literature, geography, history and culture.